Fe 3 C nanoparticles for magnetic hyperthermia application - Gangwar A.; Varghese S.S.; Meena S.S.; Prajapat C.L.; Gupta N.; Prasad N.K. (My University, 2025)
Fe 3 C magnetic nanoparticles were synthesized by solvothermal assisted technique. The X-ray and electron diffractions have confirmed the formation of monophasic iron carbide (Fe 3 C) nanoparticles. Transmission electron microscope analysis validated that the size of the particles was around 19–34 nm. The presence of only Fe and C in Fe 3 C was asserted by X-ray photoelectron spectroscopy (XPS). The room temperature Mössbauer spectroscopy also corroborates the occurrence of only this carbide phase. The saturation magnetization at ±2 T and at 300 K was obtained to be around 88 Am 2 /kg with a coercivity of 17.3 mT and remanence of 6 Am 2 /kg. The oleic acid based ferrofluid of this carbide nanoparticles exhibited good heating ability in the presence of external alternating current (AC) magnetic fields. The optimum specific absorption rate and intrinsic loss power values were 85 W/g and 0.97 nHm 2 /kg at 23 mT and 261 kHz. Due to lack of reports on magnetic hyperthermia response for iron carbides, the values were compared with iron oxides. The values were found to be comparable. © 2019 Elsevier B.V.